The salt of Costa Chica in Guerrero (Mexico) and Colan in Piura (Peru). Some comparative ethnohistorical proposals - Quiroz Malca, Haydee (2018)
In this article I am interested in presenting some comparative approaches on salt and its traditional artisanal production in Mexico and Peru, from ethnohistory and certain mythical constructions, taking as analytical ethnographic spaces Costa Chica in Guerrero and Colán on the northern coast of the department of Piura. In both cases the importance of this precious item gives us insights on the various economic, social, political and symbolic uses attributed to salt.